Giant Rhinolith (A Report of 3 Cases) - I. N. Tiwari; K. R. Gupta; W. Seethavam; K. S. Mehdiratta (Indian Journal of Plastic Surgery, 1977)
Three cases of giant rhinoliths are described causing destruction of the nasal septum and lateral wall of the nose. No previous history of foreign body was present. The association of rhinolith with cleft lip and palate is uncommon.